Pathogenesis of respiratory syncytial virus bronchiolitis-related wheezing. - Psarras,S; Papadopoulos,NG; Johnston,SL (Paediatr Respir Rev, 2004)
Respiratory syncytial virus (RSV) is a common cause of virus infection of the human respiratory tract during the first two years of life, with virtually all children experiencing at least one infection within this period. Although this usually leads to mild respiratory illness, some infants develop more severe disease (bronchiolitis, pneumonia, etc.) affecting the lower airways and frequently requiring hospitalisation. There is evidence that bronchiolitis hospitalisations have increased during the last two decades and many of the hospitalised children develop wheezing later in life. The immune response to the virus is probably a major factor in the development or the expression of the pathological phenotype. In particular, a bias towards type-2 cytokine responses seems to be associated with more severe disease, whereas a type-1 response leads to more effective viral clearance and milder illness. Although the virus by itself triggers a type-1 response, a preexisting type-1 deficiency may contribute to the severity of the disease. In that sense, RSV bronchiolitis may serve as a marker, reflecting predisposition of the individual for virus induced wheezing early in life and/or asthma later in life.